Pre-clinical markers for diagnosis of diabetic nephropathy in patients with type 1 diabetes mellitus - Nadezhda Olegovna Lebedeva (Endocrinology Research Centre, 2012)
Due to progressive nature of diabetic nephropathy (DN) and limited effectiveness of therapeutic efforts at clinically overt stages, diagnosisof pre-clinical (and, therefore, potentially reversible) DN is especially important. To date, however, test for microalbuminuriaremains the only technique applicable for early diagnostics of DN. Current review addresses search for potential markers of pre-clinical stage of DN in patients with type 1 diabetes mellitus and embracesdata from latest experimental and clinical studies in this area.